The role of auditory abilities in basic mechanisms of cognition in older adults - Grassi, Massimo; Borella, Erika (Frontiers in Aging Neuroscience, 2013)
The aim of this study was to assess age-related differences between young and older adults in auditory abilities and to investigate the relationship between auditory abilities and basic mechanisms of cognition in older adults. Although there is a certain consensus that the participant’s sensitivity to the absolute intensity of sounds (such as that measured via pure tone audiometry) explains his/her cognitive performance, there is not yet much evidence that the participant’s auditory ability (i.e., the whole supra-threshold processing of sounds) explains his/her cognitive performance. Twenty-eight young adults (age < 35), 26 young-old adults (65 ≤ age ≤75) and 28 old-old adults (age > 75) were presented with a set of tasks estimating several auditory abilities (i.e., frequency discrimination, intensity discrimination, duration discrimination, timbre discrimination, gap detection, amplitude modulation detection, and the absolute threshold for a 1 kHz pure tone) and the participant’s working memory, cognitive inhibition, and processing speed. Results showed an age-related decline in both auditory and cognitive performance. Moreover, regression analyses showed that a subset of the auditory abilities (i.e., the ability to discriminate frequency, duration, timbre, and the ability to detect amplitude modulation) explained a significant part of the variance observed in processing speed in older adults. Overall, the present results highlight the relationship between auditory abilities and basic mechanisms of cognition.